2012
DOI: 10.1016/j.plantsci.2011.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Modifying crops to increase cell wall digestibility

Abstract: Improving digestibility of roughage cell walls will improve ruminant animal performance and reduce loss of nutrients to the environment. The main digestibility impediment for dicotyledonous plants is highly lignified secondary cell walls, notably in stem secondary xylem, which become almost non-digestible. Digestibility of grasses is slowed severely by lignification of most tissues, but these cell walls remain largely digestible. Cell wall lignification creates an access barrier to potentially digestible wall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
113
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 139 publications
(120 citation statements)
references
References 160 publications
(222 reference statements)
3
113
0
4
Order By: Relevance
“…It is also possible to compromise switchgrass plant fitness (winter survival) by repeated selection for increased in vitro dry matter forage digestibility (as a proxy for ruminant digestion; [38]) in northerly adapted populations as a consequence of lowering lignin content of the biomass [39]. Although such selection did not lead to changes in the timing of plant developmental responses, such as green-up and flowering dates, populations with lower plant lignin had greater winter kill.…”
Section: Molecular Mechanisms Impacting Senescence Dormancy and Tillmentioning
confidence: 99%
“…It is also possible to compromise switchgrass plant fitness (winter survival) by repeated selection for increased in vitro dry matter forage digestibility (as a proxy for ruminant digestion; [38]) in northerly adapted populations as a consequence of lowering lignin content of the biomass [39]. Although such selection did not lead to changes in the timing of plant developmental responses, such as green-up and flowering dates, populations with lower plant lignin had greater winter kill.…”
Section: Molecular Mechanisms Impacting Senescence Dormancy and Tillmentioning
confidence: 99%
“…It has increasing genetic resources (JGI Phytozyme 2016) and the strong potential to be grown with low inputs (McLaughlin and Adams Kszos, 2005; U.S. Department of Energy – Office of Biological and Environmental Research 2014). Understanding factors that influence recalcitrance is critical to improve switchgrass and other feedstocks as bioenergy fuel sources and multiple cell wall biosynthesis gene targets for improving plants via breeding and biotechnology have been discussed (Jung et al ., 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Improta and 22 Kellens (2001) reported that processing (polishing or washing) of quinoa prior to feeding, or 23 diluting the quinoa with some other available feed are viable options that can be considered for 24 improving performance of broilers when quinoa is a major component of the diet. 2 The herbage samples were immediately dried in a forced-draft air oven to a constant weight 3 and the drying temperature was set at 65°C. The samples were then brought to air temperature, 4 weighed, ground in a Cyclotec mill (Tecator, Herndon, VA, USA) to pass through a 1 mm screen 5 and stored for qualitative analyses.…”
mentioning
confidence: 99%